The influence of competency, professionalism, good organizational communication, and team work on individual performance - Muchtamim, Muchtamim (Journal of Economics and Business Letters, 2026)
This study examines the influence of competency, professionalism, good organizational communication, and teamwork on employee performance among private company employees in Jakarta. Data were collected through questionnaires distributed via Google Forms. Using the Lamshow formula, the required sample size was 96.04 and rounded to 97 respondents. An initial validity and reliability test on 30 samples showed all items were valid (r > 0.312) and reliable (Cronbach’s alpha > 0.60). Classical assumption tests indicated that the data were normally distributed, with no multicollinearity (VIF < 10; tolerance > 10%) and no heteroscedasticity based on scatterplot results. Simple and multiple regression analyses revealed that competency, professionalism, good organizational communication, and teamwork partially and simultaneously have positive and significant effects on employee performance. The coefficients of determination showed that competency contributed 46.8%, professionalism 50.6%, organizational communication 33.9%, teamwork 56.4%, and all variables simultaneously 70.1% to employee performance.